PKM Pendampingan Literasi Kritis melalui Pemanfaatan Teknologi dan Informasi Digital bagi Siswa di SMK Farmasi Mandala Tiara Bangsa Jakarta - Khusnul Fatonah; Sri Lestari; Deny Surya Saputra (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Literacy habits carried out in schools have not been able to improve students' critical thinking skills at SMKF Mandala Tiara Bangsa Jakarta. Lack of mastery of technology also causes students' reluctance to look for valid reference sources of information. The solution to these problems is the need for critical literacy assistance through the use of technology and digital information for students at the SMKF Mandala Tiara Bangsa Jakarta. The method of this activity is observation, interview, presentation, discussion, question and answer, and practice (simulation). This activity is carried out in two stages. The first stage is sharing knowledge about critical literacy, including strategies for finding trusted reference sources. The second stage is the practice of critical literacy which is carried out in groups. The activity closed with an evaluation between the abdimas team and the participants and accompanying teachers. The result of this activity is that students are able to apply critical literacy well. Students can also seek the truth of information through trusted sources with the help of technology and digital information. Although the verbal delivery of information has not been maximized, students will learn to improve their self-confidence better, especially when speaking in public.